Current knowledge of Lyme disease’s pathogenesis - N. V. Skripchenko; A. A. Balinova (Журнал инфектологии, 2014)
This review present current immunological, microbiological and molecular genetic features of Lyme disease. The mechanisms of borrelia’s dissemination and adaptation in the macroorganism are describe. The role of B. burgdorferi s.l. in the development of autoimmune diseases and non-Hodgkin-lymfomas is describe.